Maria z Bochdanów Obertyńska, jej rodzina i środowisko. Próba rekonstrukcji zaginionego świata kresowych rodów = Maria of the Bochdans Obertyńska, family and environment. Attempt of reconstruction of the lost world of the borderland families - Jazownik, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The history of two families of the landed gentry, Bochdans and Obertyńskis, who had lived at the area of the Eastern Lesser Poland for several centuries, until the end of the Second Republic of Poland, have been outlined in the article. The article describes in particular persons and events related to Maria of the Bochdans Obertyńska (1861-1956), the author of memoirs from the period of the First World War, published in 2012 under the title "Pamiętnik Galicjanki" (Galicjan`s Diary) "(1914-1917)" and incorrectly attributed to Magdalena Bylczyńska (1887-1966).
Keywords: Polish diary keeping; landed gentry; Eastern Galicia; the Bochdans (family); theObertynskis (family); pamiętnikarstwo polskie; ziemiaństwo; Galicja; Bochdanowie (rodzina); Obertyńscy (rodzina)